CHARACTER EDUCATION VALUES IN THE SAPARAN TRADITION FOLKLORE ON WRITING SKILLS LEARNING - Yanuar Bagas Arwansyah; Sarwiji Suwandi; Sahid Teguh Widodo (Fakultas Bahasa dan Seni UNP, 2017)
AbstractThis study aims to describe the value of character education of folklore in the Saparan tradition for the improvement of writing skills on learning in High School. This type of research is descriptive qualitative by deepening the history and education value through direct observation, interview, and document analysis. The validity of this study used triangulation of data and sources. Based on the results of analysis using Roland Barthes's semiotics theory validated by in-depth interviews, it is concluded that the values of character education in this Saparan tradition are the value of social care, the value of cultural education, and religious values. The substance of this research is to provide an understanding of the history and value of folklore in the Saparan tradition as a learning material for improving writing skills.Keywords: education value ,folklore,writing skill. AbstrakPenelitian ini bertujuan mendeskripsikan nilai pendidikan karakter cerita rakyat dalam tradisi Saparan untuk peningkatan keterampilan menulis pada pembelajaran di Sekolah Menengah Atas. Jenis penelitian ini adalah deskriptif kualitatif dengan mendalami sejarah dan nilai pendidikan melalui observasi langsung, wawancara, dan analisis dokumen. Validitas penelitian ini menggunakan triangulasi data dan sumber. Berdasarkan hasil analisis menggunakan teori semiotika Roland Barthes yang divalidasi dengan wawancara mendalam, disimpulkan bahwa nilai-nilai pendidikan karakter dalam tradisi Saparan ini adalah nilai peduli sosial, nilai pendidikan budaya, dan nilai religius. Substansi dari penelitian ini adalah memberi pemahaman tentang sejarah dan nilai pada cerita rakyat dalam tradisi Saparan sebagai bahan pembelajaran untuk meningkatkan keterampilan menulis.Kata Kunci: nilai pendidikan, cerita rakyat, keterampilan menulis.